Size and value premium, performance and dynamic linkages of penny stocks in Malaysia / T. Shanmugam Thangavelu - T. Shanmugam, Thangavelu (2019)
This thesis presents three related empirical studies on: (1) performance of the Malaysian penny stocks; (2) risk-return analysis of Malaysian penny stocks; and (3) the impact of macroeconomic and non-macroeconomic determinants on Malaysian penny and non penny stocks. The period of analysis covers a total of 72 months stretching from July 2009 to June 2015 in the post-revamp period of Bursa Malaysia. The first 12-month period from July 2009 to June 2010 was set as formation period to compute a justifiable price benchmark to identify penny stocks and to further construct relevant portfolios. This research adopted the criteria of stocks with the price of RM0.31 and below to be penny stocks (Pr ? RM0.31) while the rest are categorized as non-penny stocks (Pr > RM0.31). This study was conducted during the second 5-year period from July 2010 to 2015. The first part of the thesis deals with a comprehensive analysis of the financial characteristics and the performance of penny and non-penny stocks during the study period. The findings reveal that Malaysian based penny stocks are characterized by smaller market capitalization, higher beta, higher book-to-market ratio, and higher idiosyncratic volatility on the average. The second part of the research undertakes to verify the variation of risk premiums in each portfoliosï¿½ rate of return with differing asset pricing models. Three findings have emerged: (1) The magnitude of change in portfolio alphas of penny and non-penny stocks are marginal and economically small to explain the return variations in the respective portfolios; (2) All risk premiums except profitability factor are significant; (3) The single factor CAPM, 3-factor, 4-factor and 5-factor models are significant and able to capture the return variations for penny stocks. The compounding implication of knowing the prominent risk premium can be exploited for trading strategies of penny stocks in an effort to gain abnormal returns by potential investors. The third study examined the relationships between selected macroeconomic and non-macroeconomic variables with penny and non-penny stocksï¿½ returns by using the ARDL bounds testing for cointegration. The direction of the causality between the variables were investigated by applying the VECM Granger causality approach. The results have revealed that the variables are cointegrated for long-run relationship. Independent macroeconomic variables of GDP and price index of Malaysia together with non-macroeconomic forces representing political events and global oil price plunge moves in tandem with the hypothesized reaction to the returns of penny stocks. As for the short-run elasticities, the coefficient of the ECMt-1 for all independent variables are significant and reinforces the existence of the long-run relationship among the variables. The causality analysis confirms the existence of unidirectional causality from all independent variables to the returns of dependent variables in the long-run with the statistically significant ECTt-1. The GDP and the stock price index of Malaysia are a significant Granger-cause to the returns of all price sorted portfolios in the short- and long-run. The empirical results of this study may be used as valuable information by local and global stock investors in developing a view of the Malaysian economy and to facilitate their financial and investment planning process.